2022
DOI: 10.4236/ajps.2022.137069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturity Indices on Growth and Quality of High Value Vegetables

Abstract: The study took place at Bangladesh Agricultural Research Institute's Olericulture Division's research farm from March 2021 to February 2022 (BARI). In a protected net house, we investigated the impact of five different types of vegetables on various maturation stages, including tomato, broccoli, sweet pepper, cucumber, and netted melon. Vegetables cultivated under protected conditions in a transparent poly-film net house can improve quality, maturity, fruit size, and yield. When fruits and vegetables are picke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…This difference could be attributed to the fact that the lettuces harvested at 58 DAP reached their optimal maturity, allowing them to maintain a superior appearance, and have lower rates of wilting and shrivelling, fewer defects, and reduced decay, all while preserving a higher level of freshness compared to the other maturity stages. These findings are consistent with those of Quamruzzaman et al (2022), who emphasized the significance of optimum maturity indices in influencing the growth and quality of high-value vegetables. Vietnam Journal of Agricultural Sciences Note: Vertical bars represent the standard error of the mean of three replications.…”
Section: Sensory Qualitysupporting
confidence: 92%
See 2 more Smart Citations
“…This difference could be attributed to the fact that the lettuces harvested at 58 DAP reached their optimal maturity, allowing them to maintain a superior appearance, and have lower rates of wilting and shrivelling, fewer defects, and reduced decay, all while preserving a higher level of freshness compared to the other maturity stages. These findings are consistent with those of Quamruzzaman et al (2022), who emphasized the significance of optimum maturity indices in influencing the growth and quality of high-value vegetables. Vietnam Journal of Agricultural Sciences Note: Vertical bars represent the standard error of the mean of three replications.…”
Section: Sensory Qualitysupporting
confidence: 92%
“…Similarly, the research conducted by Gil et al (2012) supports our findings, as it indicated that immature vegetables experience greater water loss, resulting in wrinkling and diminished flavor quality. Quamruzzaman et al (2022) underscored the importance of harvesting vegetables and fruits at appropriate stages of maturity, as their study suggested that immature produce is prone to shrivelling, mechanical damage, and developing poor color, flavor, and taste resulting in a loss of consumer confidence.…”
Section: Sensory Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the dry matter content, which is essential for the quality of the fruit and has a beneficial effect on the taste qualities of the produce, was found to be within the normal range of 5 to 7.5% [24]. The rest of the quality parameters, including weight, size, colour, and firmness, showed similar values to those previously established in the same or others tomato varieties [25,26], except the weight of the Karelya and Muchamiel varieties, which were higher than those established by other authors [27,28].…”
Section: Discussionmentioning
confidence: 62%